A Note on the Multiple Seeded Rice of India - Chowdhury, N. P. (Indian Forester, 1949)
A multiple seeded variety of paddy (Oryza sativa L. var plena Prain) is recorded from parts of India, where it is not regarded merely as a curiosity, but is under regular cultivation (Districts of Gaya, Singhbhum, Ranchi). The variety gives a good yield and possesses grains (light red coloured) of a fine type. The suspected occurrence of the prehistoric husk impressions of this type on pottery from the Khokra Kot mounds of Rohtak (Sahni I.c.) its present restricted distributions its occurrence in China, coupled with the occasional appearance of multiple ovaries in normal paddy (Hedayatullah I.c.) (to be regarded as reversions to the original multipistillate condition) suggest its antiquity and primitive nature and seem to justify its assignment to a separate species. e.g., O. plena (Prain) Chowdhury. I am deeply indebted to Prof. D. Rhind, I.A.S., formerly Professor of Agricultural Botany, Agricultural College, Mandalay (Burma) and Prof. P. Maheshwari, D.Sc., F.N.I., Professor of Botany, Delhi University for kindly going through the manuscript and for the valuable criticisms offered. I am also very thankful to Mr. M.B. Raizada of the Forest Research Institute and College, Dehra Dun and Dr. D. Chatterjee of the Indian Agricultural Research Institute, New Delhi for helpful suggestions and their kind interest in this work.